Does Motivation Impact OCD Symptom Severity? An Exploration of Longitudinal Effects. Issue 2 (March 2019) - Ponzini, Gabriella; Van Kirk, Nathaniel; Schreck, Meghan; Nota, Jacob A.; Schofield, Casey A.; Gironda, Christina; Elias, Jason
Abstract: Understanding the role of patient motivation in OCD treatment is of clinical importance given the requisite autonomous role of patients in Exposure and Response Prevention. The present study investigated state- and trait-like relations between three variables: two previously established motivational constructs, readiness to change (RTC) and committed action (CA), derived from the University of Rhode Island Change Assessment, and OCD symptom severity as measured by the self-report Yale-Brown Obsessive Compulsive Scale ( Y-BOCS-SR). Utilizing a random-intercept cross-lagged panel model (RI-CLPM) design, we assessed autoregressive, within-time correlations, and cross-lagged effects of RTC, CA, and Y-BOCS-SR scores at admission, month 1 of treatment, and discharge from an intensive/residential treatment program for OCD. Results revealed significant autoregressive (i.e., state-like) effects for CA and Y-BOCS-SR, negative within-time correlations between state CA and Y-BOCS-SR across all time points, a positive within-time correlation between state CA and RTC at admission, and a cross-lagged effect between state Y-BOCS-SR at month 1 of treatment and state RTC at discharge. Results also demonstrated that the stability of the RTC variable was attributable to trait-like factors in the present sample. This study is novel in its use of RI-CLPM in an OCD sample and represents an important addition to the literature on the longitudinal impacts of dynamic constructs of motivation. Our findings may provide future researchers with strategies to supplement ERP with CA-driven motivational interviewing. Highlights: ERP for OCD requires motivation for successful engagement and completion Assessed longitudinal relations of motivation using dynamic constructs and OCD severity RI-CLPM found the stability of readiness to change to be trait-like and time-invariant State CA was negatively correlated with symptom severity within all measured time points Future research is needed about CA-driven motivation enhancement for ERP treatment